Deconvolution of octahedral Pt3Ni nanoparticle growth pathway from in situ characterizations. Issue 1 (December 2018) - Shen, Xiaochen; Zhang, Changlin; Zhang, Shuyi; Dai, Sheng; Zhang, Guanghui; Ge, Mingyuan; Pan, Yanbo; Sharkey, Stephen; Graham, George; Hunt, Adrian; Waluyo, Iradwikanari; Miller, Jeffrey; et al.
Abstract Understanding the growth pathway of faceted alloy nanoparticles at the atomic level is crucial to morphology control and property tuning. Yet, it remains a challenge due to complexity of the growth process and technical limits of modern characterization tools. We report a combinational use of multiple cutting-edge in situ techniques to study the growth process of octahedral Pt3 Ni nanoparticles, which reveal the particle growth and facet formation mechanisms. Our studies confirm the formation of octahedral Pt3 Ni initiates from Pt nuclei generation, which is followed by continuous Pt reduction that simultaneously catalyzes Ni reduction, resulting in mixed alloy formation with moderate elemental segregation. Carbon monoxide molecules serve as a facet formation modulator and induce Ni segregation to the surface, which inhibits the (111) facet growth and causes the particle shape to evolve from a spherical cluster to an octahedron as the (001) facet continues to grow. Understanding the growth pathway of faceted alloy nanoparticles at the atomic level is crucial to morphology control and property tuning, but remains a challenge. Here, the authors reveal the particle growth and facet formation mechanisms of octahedral Pt3 Ni nanoparticles using multiple cutting-edge in situ techniques.